The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.7162/s1809-97772013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of otorhinolaryngologic diagnoses in the pediatric emergency room

Abstract: Summary Introduction: Fever and pain, which are very common in ear, nose, and throat pathologies, are among the most frequent complaints recorded during emergency room pediatric patient treatment. Most of time, the pediatricians are called on to evaluate otorhinolaryngology disorders that requires specialist assessment. Aim: To determine the prevalence of otorhinolaryngologic diagnoses in a pediatric population in a reference hospital in the city of Itatiba, São Paulo. Methods: We evaluated 2,054 pediatric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(5 reference statements)
1
1
0
Order By: Relevance
“…Kumar and Gulati in 1999 found this proportion to be 33.7% which was much closer to the age distribution pattern in general population than the present study [3]. Signorelli and Mendes in their study found more than half of the total children attended hospital emergency were diagnosed to have one or other diagnosis related to otolaryngology [4]. In the present study the data of total pediatric emergency attendance was not included so it couldn't be commented from this study whether the ENT emergency problems among the children were proportionately more or in general the emergency medical problems were more in pediatric age group.…”
Section: Discussionsupporting
confidence: 80%
“…Kumar and Gulati in 1999 found this proportion to be 33.7% which was much closer to the age distribution pattern in general population than the present study [3]. Signorelli and Mendes in their study found more than half of the total children attended hospital emergency were diagnosed to have one or other diagnosis related to otolaryngology [4]. In the present study the data of total pediatric emergency attendance was not included so it couldn't be commented from this study whether the ENT emergency problems among the children were proportionately more or in general the emergency medical problems were more in pediatric age group.…”
Section: Discussionsupporting
confidence: 80%
“…Ear, Nose and Throat (ENT) diseases accounts for 25-40% of all hospital patients and are serious public health problems because of their universal distribution, the morbidities which they cause due to inherent physiological function that take place in head and neck region. 1,2 Consultation is the act of seeking assistance from another physician(s) or health care professional(s) for diagnostic studies, therapeutic interventions, or other services that may benefit the patient. 3 Subspecialty consultations are a necessary part of comprehensive medical care and are important in facilitating the exchange of information, knowledge and expertise between doctors that aids in better patient management.…”
Section: Introductionmentioning
confidence: 99%